How to Build A Green City. - Cherry, S. (IEEE spectrum)
This paper discusses Shanghai's plan in building the world's first sustainable city. However, pollution is a major concern in this city, so China has embarked on a bold, expensive experiment to see whether pollution and waste of all forms, not just the kind that taints the air can be drastically reduced or even eliminated. It broke ground on what it calls the world's first eco-city.